A two-loop robust controller for HIV infection models in the presence of parameter uncertainties. (April 2015) - Jo, Nam H.; Roh, Y.
Abstract: A two-loop robust nonlinear controller is proposed to deal with uncertain model parameters in HIV infection models, which are described by nonlinear differential equations of three state variables and antiretroviral drugs. The treatment goal is to suppress the concentration of infected CD4+ T cells to a target value using only the measurement of total CD4+ T cell concentration. The outer-loop controller is designed to achieve the treatment goal for the nominal HIV infection model, while a nonlinear disturbance observer (DOB) controller is employed in the inner-loop to compensate for parameter uncertainties. In the nonlinear DOB controller, a disturbance signal, equivalent to the parameter variation in terms of effect on the output, is canceled by its estimate. Numerical simulations verify that the proposed controller achieves robust performance for reducing the concentration of infected CD4+ T cells even in the presence of parameter uncertainties.